Leading learning and teaching via teacher-student and peers’ communicative activities in the classrooms - Khushik, Ghulam Abbas (2020)
Teachers and students are the inseparable part of classrooms that have teaching and learning roles in the classrooms. Leadership is an additional role of the teachers and students in the classrooms. That leadership comes in to practice in learning and teaching into classes via verbal and nonverbal communications in the classrooms. The purpose of the current study is to explore leading learning and teaching via teacher-student and peers' communicative activities. Accurately, the leadership role in teacher-student and peers' verbal and nonverbal communications in the classrooms. The target of the current research is to discover the understudied interactions of teachers and students in which they represent their leadership role in the classes. The videos of three full-length lectures on three different subjects at three different times were recorded for communicational analysis. The themes are extracted with thematic analysis in qualitative methods to discover the displayed leadership roles in teacher-student verbal and nonverbal communications in the classrooms. The main results inform that there are verbal and nonverbal communicative activities reflecting the leadership role, which plays a vital role in learning and teaching. The findings contribute to the strand of leadership and communication research. Similarly, it presents the results applicable to classroom communications in contexts other than Finland.